Duration, score, and timing: factors influencing the success of offensive transitions in top, marginal, and emerging football leagues - Eusebio, Pedro; Prieto-González, Pablo; Marcelino, Rui (Frontiers in Sports and Active Living, 2025)
ObjectiveThe study aimed to increase our understanding of offensive transitions in football, focusing on the time spent executing them and how it is influenced by the period in which they occur and the instant score. The objective is to understand its temporal variables and how they influence the unfolding of the scoreline during a match.MethodologyThis study analyzes 1,649 goals resulting from offensive transitions in 1,151 games across three leagues categories: Top, Marginal, and Emerging leagues. Multinomial logistic regression was performed to understand associations and predictors between the variables: “duration of a transition”, “Time of offensive transition occur” and the “score at the moment”.ResultsThe research reveals that, across all league categories, the last 15 min of the first and second halves, have the highest frequency of successful offensive transitions, particularly on the last 15 min of matches. In Top leagues, 69% of offensive transitions last for 9 s or more, with slower transitions more prevalent towards the end of games. In Marginal leagues, 41% of successful transitions took 13 s or longer, while in Emerging leagues, 53% of successful offensive transitions occurred when the game was not in a 0–0 state. The results show associations between all variables in Top Leagues. No associations were found in Marginal leagues. Associations between duration of the transition and the time of the game they occur were found on Emerging Leagues.ConclusionThese findings underscore the importance of tailored strategic plans for offensive transitions, to optimize scoring opportunities and performances.